Evaluation of Treatments in Patients with Nocturnal Bruxism on Bite Force and Occlusal Contact Area: A preliminary report - Alkan, Alper; Bulut, Emel; Arici, Selim; Sato, Shuichi (European Journal of Dentistry, 2008)
Objectives: The purpose of this study was to investigate the short-term effects of occlusal splint therapy and tricyclic antidepressants on the bite force and occlusal contact area of patients presenting with nocturnal bruxism.Methods: A maxillary full-coverage hard acrylic splint was applied to the five patients (Group S). Five patients took a tricyclic antidepressant (Amitriptiline HCl, 10 mg/day) for 3 months (Group A) and a control group (Group C) comprising of 10 dental school students with normal occlusion was also formed. Using a Dental Prescale (Fuji Photo Film Corporation, Tokyo, Japan) and an Occluzer computer (FPD703, Fuji Photo Film Corporation, Tokyo, Japan) the bite force and occlusal contact area were measured. The evaluations were made just before the treatment and at 1 month and 3 months of treatment.Results: The bite force and occlusal contact area before treatment in study Groups A and S were found to be higher than those in the Group C. Furthermore, the bite force and occlusal contact area increased during treatment in Group A whilst they decreased in Group S. Bite force and occlusal contact area in Group S were lower at both 1 month and 3 months of treatment than in Group C.Conclusions: It could be tentatively suggested that occlusal splint therapy may be more effective than tricyclic antidepressant in the treatment of bruxism. Further investigations of this measurement method involving larger study populations and a longer follow-up period are needed. (Eur J Dent 2008;2:276-282)
Keywords: Antidepressant; Bite force; Bruxism; Occlusal contact area; Splint